2011
DOI: 10.1186/1297-9716-42-103
|View full text |Cite
|
Sign up to set email alerts
|

Increase of cells expressing PD-L1 in bovine leukemia virus infection and enhancement of anti-viral immune responses in vitro via PD-L1 blockade

Abstract: The inhibitory receptor programmed death-1 (PD-1) and its ligand, programmed death-ligand 1 (PD-L1) are involved in immune evasion mechanisms for several pathogens causing chronic infections. Blockade of the PD-1/PD-L1 pathway restores anti-virus immune responses, with concomitant reduction in viral load. In a previous report, we showed that, in bovine leukemia virus (BLV) infection, the expression of bovine PD-1 is closely associated with disease progression. However, the functions of bovine PD-L1 are still u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
95
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 38 publications
6
95
1
Order By: Relevance
“…In further experiments, anti‐virus cytokine production was reduced as was shown in our previous reports 23, 24, 28. Moreover, CD4 + CD25 high Foxp3 + T cell numbers were increased in conjunction with increasing proportions of TGF‐β‐secreting CD4 + CD25 high Foxp3 + T cells, leading to correlations with increased proviral loads in BLV‐infected cattle, as shown previously 25, 26.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In further experiments, anti‐virus cytokine production was reduced as was shown in our previous reports 23, 24, 28. Moreover, CD4 + CD25 high Foxp3 + T cell numbers were increased in conjunction with increasing proportions of TGF‐β‐secreting CD4 + CD25 high Foxp3 + T cells, leading to correlations with increased proviral loads in BLV‐infected cattle, as shown previously 25, 26.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, cell‐mediated immune dysfunction accelerates disease progression during BLV‐infection as indicated in previous studies showing that IFN‐γ plays important roles in protective mechanisms against BLV propagation in infected animals 23, 24, 28. In addition, the ensuing immune disorder may contribute to the development of opportunistic infections in BLV‐infected cattle 31, 32.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…paratuberculosis-infected cattle. In previous studies, we showed that inhibition of PD-1/PD-L1 and LAG-3/MHC-II pathways by blocking antibodies reactivates IFN-␥ responses in PBMCs of BLV-infected cattle (13,15,16). Thus, in the present study, we determined whether IFN-␥ responses to M. avium subsp.…”
Section: Paratuberculosis-infected Groupmentioning
confidence: 82%
“…Moreover, blockade of these inhibitory pathways restores exhausted T-cell function and induces antiviral responses in vitro (13,15,16). However, it remains unclear whether PD-1 and LAG-3 pathways are involved in the development of T-cell exhaustion in other chronic infections of cattle.…”
mentioning
confidence: 99%